(3TQM JLQjO GdcdGes - (3eLghds ((3edG eMeO Hf CbG edcs)
(3ChdgG (B:s
(3HSe Gddg (B... (3GdebUO GdKGdK aj EKHGJ GdUGfY hUaGJg hBKGQg hajg aUhd ; GdaUd GdChd aj hLhOg JYGdi GdehLhO Ef cGf hGLHG agh GdeWdhH hEdG GSJdReg dGSJMGdI (B...s
(3BNQgG (B:s
... (3Ke Efg aQV caGjI dG aQV Yjf aEPG bGe Hg bhe SbW Yf GdBNQjf hEPGXf cd WGFaI Cfg jbe Hg GdBNQ CKe Gdcd HJQcg gPG BNQ eG JjSQ(B.s
(3HBNQgG ahGFO HGdYQHjI hGdaGQSjIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3GdJhMjO hGdedd hGdfMds